Corrosion behavior of mild steel in seawater from two different sites of Kuala Terengganu coastal area - Wan Nik, Wan Mohd Norsani; F., Zulkifli; Rahman, Md. Mokhlesur (I J E N S Publishers, 2011)
Corrosion behavior of mild steel in seawater from different sites was investigated by using weight loss method and potentiodynamic polarization test. Samples were immersed at two different sites near Kuala Terengganu coast and analyzed for its parameters. There is slight difference of corrosion behavior from both sites. Samples immersed in site 1 gave higher corrosion rate and corrosion current densities (icorr) while the value of corrosion potential, Ecorr for site 1 shifted to negative region which indicates the increasing of corrosion activity. Small differences of seawater parameters causes the corrosion behavior of mild steel from both sites to be same where all the plots recorded shows the same pattern.